Intimate partner violence victimization during the COVID-19 pandemic among a global online sample of sexual minority men - Hong, Chenglin (Journal of family violence, 2023)
Purpose: We aimed to describe the prevalence of IPV victimization, changes of experiencing IPV victimization, and examined factors associated with more severe or frequent IPV victimization since the COVID-19 crisis among a global sample of sexual minority men (SMM). Methods: Data were collected between October and November 2020 through a gay social networking (GSN) application. We used multinominal logistic regression to examine correlates of experiencing any IPV during the pandemic and experiencing more severe or frequent IPV since the pandemic began. Results: Of all participants (n = 9420), IPV victimization prevalence in the past 6 months was 17.0%, 19.5% of whom reported experiencing more severe or frequent IPV and 55.7% reported experiencing IPV that stayed the same since the COVID-19 started. Experiencing more severe or frequent IPV victimization since the pandemic began was associated with having engaged in sex work, having an income reduction by more than 20% and cutting meals since the COVID-19 crisis began. Increased tobacco use and psychological distress were also associated with increased IPV victimization. Lastly, SMM who reported having met a sexual partner through GSN apps were more likely to say that their experience of IPV had been more severe or frequently. Conclusion: Our results demonstrate relatively high levels of reporting IPV victimization during the COVID-19 pandemic among a global sample of SMM. The findings illustrate an increasing need for IPV resources and programs as the pandemic continues to evolve. New technologies such as GSN apps have the potential to deliver confidential and safe IPV screening, services, and resources.